2013
DOI: 10.1002/jat.2942
|View full text |Cite
|
Sign up to set email alerts
|

Calcium montmorillonite clay reduces AFB1 and FB1 biomarkers in rats exposed to single and co‐exposures of aflatoxin and fumonisin

Abstract: Aflatoxins (AFs) and fumonisins (FBs) can co-contaminate foodstuffs and have been associated with hepatocellular and esophageal carcinomas in humans at high risk for exposure. One strategy to reduce exposure (and toxicity) from contaminated foodstuffs is the dietary inclusion of a montmorillonite clay (UPSN) that binds AFs and FBs in the GI tract. In this study, the binding capacity of UPSN was evaluated for AFB1, FB1 and a combination thereof in Fischer-344 rats. Rats were pre-treated with different dietary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 60 publications
(80 reference statements)
3
26
1
2
Order By: Relevance
“…Importantly, these results suggest that lead should not be significantly bioavailable from this clay following ingestion by humans and animals. This conclusion is further supported by our earlier animal and human intervention studies, that showed no significant increase in serum lead levels following ingestion of CM clay as high as 2.0% in the diet [47].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Importantly, these results suggest that lead should not be significantly bioavailable from this clay following ingestion by humans and animals. This conclusion is further supported by our earlier animal and human intervention studies, that showed no significant increase in serum lead levels following ingestion of CM clay as high as 2.0% in the diet [47].…”
Section: Discussionsupporting
confidence: 75%
“…The hydra assay showed the increased binding ability of APMs compared to parent montmorillonites and established the safety of APMs at inclusion levels as high as 2% w/v. It is possible that APMs at higher inclusion will result in more significant protection against toxicity based on previous dosimetry studies [47,49,50]. Importantly, we have used this organism to select optimal sorbents for food-borne and environmental toxicants, prior to safety and efficacy studies in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…The purified AFB 1 adducts were eluted with 2% formic acid in methanol, dried in a CentriVap concentrator (Labconco Corp., Kansas City, MO), and reconstituted for HPLC fluorescence detection. Adduct concentrations were adjusted to total plasma albumin content to account for variations in volume (Sabbioni et al, 1990;Qian et al, 2013;Mitchell et al, 2014).…”
Section: Bw Sample Collection and Analysismentioning
confidence: 99%
“…In spite of these abilities, which imply putative roles in the intestinal microenvironment, studies have been rarely conducted for the effects of bentonite on intestinal microorganisms. The preventive effects of bentonite against various health problems, such as hepatocarcinoma and renal disease through absorption and excretion of mycotoxins such as aflatoxin and uric acid, have been demonstrated in previous studies. Recently, the anti‐obesity effects of bentonite were examined by Xu et al .…”
Section: Introductionmentioning
confidence: 75%